Replication Data for "Intergenerational Nutrition Benefits of India's National School Feeding Program" - International Food Policy Research Institute; University of Washington (International Food Policy Research Institute, 2021)
National Family Health Survey (NFHS-4) is a national, state, and district representative sample of 601,509 households with a response rate of 97.6%. In all households, women age 15-49 are eligible to participate. The study focuses on a sample of over 200,000 women with a mean age of 26.8 years who had a living child in the 5 years preceding the survey (N=196386, 48% female, 52% male). The exposure variable was obtained from the National Sample Survey-Consumer Expenditure(NSS-CES) rounds 50 (1993/94), 55 (1999/00), 61 (2004/05), and 69 (2011/12). The NSS-CES cross-sectional surveys are representative at the national and state levels. The NSS-CES survey over 100,000 households in each round and provide information on demographic characteristics of all household members. The study used data on free meals obtained at schools, among girls aged 6-10 years, to calculate the exposure to the Mid-day Meal (MDM) program by state, socioeconomic status (SES), and birth-year. The India Human Development Survey (IHDS) is a panel survey of 42,152 households. It provided data on school meals and education and the height of direct beneficiaries.